2022
DOI: 10.1111/liv.15252
|View full text |Cite
|
Sign up to set email alerts
|

Impact of NAFLD on the outcome of patients with chronic hepatitis B in Asia

Abstract: Hepatitis B virus (HBV) infection and nonalcoholic fatty liver disease (NAFLD) are two major causes of chronic liver disease (CLD) that can cause liver cirrhosis and hepatocellular carcinoma (HCC). 1,2 Although vaccination has dramatically reduced new HBV infection, WHO estimated 3.5% of the population worldwide (257 million people) were chronically infected with HBV in 2015. 3 Most Asian regions are medium to high prevalence areas of HBV infection. 4 Nowadays, NAFLD is the most common CLD in the world, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 80 publications
1
15
0
Order By: Relevance
“…Nevertheless, patients with CHB with coexisting components of MetS are associated with more severe liver diseases. Li et al have reported that fatty liver was significantly associated with higher HBsAg seroclearance in patients with CHB (28), while concurrent NAFLD might inhibit HBV replication and promote HBsAg seroclearance (29). However, the fatty liver also exacerbates liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, patients with CHB with coexisting components of MetS are associated with more severe liver diseases. Li et al have reported that fatty liver was significantly associated with higher HBsAg seroclearance in patients with CHB (28), while concurrent NAFLD might inhibit HBV replication and promote HBsAg seroclearance (29). However, the fatty liver also exacerbates liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the prevalence of histologically diagnosed NAFLD in patients with CHB rose from 11.2% in 2005 to 32.5% in 2015 in mainland China, and was as high as 39.6% in Hong Kong. 42 Interestingly, patients with CHB appear to have a lower prevalence and incidence of NAFLD than the general population, and concurrent NAFLD may promote the clearance of hepatitis B surface antigen from serum and inhibit HBV replication. 43 However, there is such a synergistic effect of NAFLD and CHB on liver disease progression that severe steatosis and steatohepatitis can exacerbate liver fibrosis in patients with CHB.…”
Section: Chronic Hepatitis Virus Carriers In Chinese Patients With Na...mentioning
confidence: 99%
“…43 However, there is such a synergistic effect of NAFLD and CHB on liver disease progression that severe steatosis and steatohepatitis can exacerbate liver fibrosis in patients with CHB. 42,43 The impact of NAFLD on HCC risk in patients with CHB is controversial, and the mechanism of interaction between HBV infection and NAFLD remains unclear. Nevertheless, patients with CHB should be closely monitored for coexisting NAFLD or NASH and receive lifelong metabolic management for a better prognosis.…”
Section: Chronic Hepatitis Virus Carriers In Chinese Patients With Na...mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Yang et al reviewed the epidemiology of concurrent NAFLD in Asian CHB patients focusing on the impact on clinical outcomes 7 . CHB patients tend to have lower prevalence and incidence of NAFLD than the general population.…”
Section: Non‐alcoholic Fatty Liver Diseasementioning
confidence: 99%